2021
DOI: 10.1021/acs.inorgchem.1c02099
|View full text |Cite
|
Sign up to set email alerts
|

Organoamine-Directed Assembly of 5p–4f Heterometallic Cluster Substituted Polyoxometalates: Luminescence and Proton Conduction Properties

Abstract: The assembly of heterometallic cluster substituted polyoxometalates (POMs) remains a great challenge for inorganic synthetic chemistry up to now. Herein, a series of 5p–4f heterometallic cluster substituted POMs were successfully isolated by a facile one-step hydrothermal reaction method, namely H17(H2en)3[SbIII 9SbVLn3O14(H2O)3]­[(SbW9O33)3(PW9O34)]·28H2O­(1-Ln, Ln = Ce, Sm, Eu, Gd, Tb, Dy) (en = ethylenediamine). Interestingly, by replacing en with imidazole, another series of 5p–4f heterometallic cluster su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…As shown in Figure a,b, conductivity depends closely on the specific RH at 35 °C. The value increased from 4.8 × 10 –4 (55% RH) to 1.2 × 10 –3 S cm –1 (70% RH), which is superior to the conductivity of most reported proton-conductive POMs under similar conditions. With increasing temperature, the conductivity increased rapidly and achieved 1.2 × 10 –2 S cm –1 as the maximum at 85 °C (Figure c,d), which is among the highest proton conductivities yet found in POM-based materials under similar operating conditions (Table S4), holding great prospects as solid electrolytes in proton-exchange membrane (PEM) fuel cells. ,,, The research data has shown that the proton-conductive performance of DMA-KNaLi-As 10 is heavily affected by a combined impact of temperature and RH. Clearly, the proton transport in DMA-KNaLi-As 10 might be markedly enhanced under hot and humid environments.…”
Section: Resultsmentioning
confidence: 85%
“…As shown in Figure a,b, conductivity depends closely on the specific RH at 35 °C. The value increased from 4.8 × 10 –4 (55% RH) to 1.2 × 10 –3 S cm –1 (70% RH), which is superior to the conductivity of most reported proton-conductive POMs under similar conditions. With increasing temperature, the conductivity increased rapidly and achieved 1.2 × 10 –2 S cm –1 as the maximum at 85 °C (Figure c,d), which is among the highest proton conductivities yet found in POM-based materials under similar operating conditions (Table S4), holding great prospects as solid electrolytes in proton-exchange membrane (PEM) fuel cells. ,,, The research data has shown that the proton-conductive performance of DMA-KNaLi-As 10 is heavily affected by a combined impact of temperature and RH. Clearly, the proton transport in DMA-KNaLi-As 10 might be markedly enhanced under hot and humid environments.…”
Section: Resultsmentioning
confidence: 85%
“…To further improve proton conductivity and stability of the composite, a polyoxometalate (POM) that is a kind of anion transition-metal oxide cluster with the characteristics of proton conduction was chosen as a guest molecule to be encapsulated into the MOF pores. , Previous studies have indicated that POM is one of the candidates for electrolyte materials in PEMFC. , Moreover, there are also some works to encapsulate POMs into the ordered channels of MOFs to achieve high proton conductivity due to supplementary proton hopping sites and increased water holding capacity …”
Section: Introductionmentioning
confidence: 99%
“…29,30 Previous studies have indicated that POM is one of the candidates for electrolyte materials in PEMFC. 31,32 Moreover, there are also some works to encapsulate POMs into the ordered channels of MOFs to achieve high proton conductivity due to supplementary proton hopping sites and increased water holding capacity. 30 Considering the aforementioned feasibility, a new strategy of preparing a proton-conducting composite (denoted as SO 3 H-IL-PMo 12 @MIL-101) based on MOF, IL, and POM with high proton conductivity is proposed (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…The design and syntheses of nanosized multinuclear coordination clusters are becoming hot topics because they promote wide applications in fields such as molecular magnetism, biosensors, nanoreactors, catalysis, quantum computing, and metal enzyme models. Although considerable progress has been made in the design and synthesis of multinuclear coordination clusters with specific structures and rich functions, studies of their self-assembly mechanisms are far from maturation. Most of the reported multinuclear coordination clusters have usually been randomly obtained through the “bottom-up” self-assembly method, which has difficulty in achieving the targeted synthesis under control through rational design. Thus, the disclosure of assembly mechanisms of multinuclear coordination clusters is especially important, which will not only help to understand the synthetic method and its rules for high-nuclearity coordination clusters but also help to endow the clusters with some specific physical and chemical properties. , At present, it is still very difficult to understand the assembly processes of coordination clusters at a molecular level. Therefore, research on the synthesis and assembly rules of coordination clusters has attracted more and more attention, but there is still a great challenge in capturing the intermediates to track the self-assembly mechanism of nanoclusters.…”
Section: Introductionmentioning
confidence: 99%